Palladium-catalyzed cross coupling reactions of 4-bromo-6H-1,2-oxazines - Zimmer, Reinhold; Schmidt, Elmar; Andrä, Michal; Duhs, Marcel-Antoine; Linder, Igor; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2009)
A number of 4-aryl- and 4-alkynyl-substituted 6H-1,2-oxazines 8 and 9 have been prepared in good yields via cross coupling reactions of halogenated precursors 2, which in turn are easily accessible by bromination of 6H-1,2-oxazines 1. Lewis-acid promoted reaction of 1,2-oxazine 9c with 1-hexyne provided alkynyl-substituted pyridine derivative 12 thus demonstrating the potential of this approach for the synthesis of pyridines.
Keywords: alkyne; halogenation; 1,2-oxazines; palladium catalysis; pyridines